Morphology and Syntax: The Relationship Between Word Formation and Sentence Structure in Indonesian Learning - Pipin Diana Sari; Imam Baehaqie; Rustono Rustono (Bahtera: Jurnal Pendidikan Bahasa dan Sastra, 2026)
This study examines the fundamental relationship between morphology and syntax in Indonesian with a focus on the process of word formation and its implications for sentence structure. Using a qualitative approach based on literature studies, the research analyzed various scientific literature to identify morphosyntactic patterns in the Indonesian language. The results of the study show that morphological processes such as affixation, reduplication, and composition have a significant impact on the syntactic function of words in sentences. Derivative affixation has proven to be the most productive in changing the category of words as well as their grammatical function. The study identified five main patterns of systematic and predictable morphosyntactic relationships. The application of generative theoretical frameworks, X-bar theory, and word-based approaches provides a comprehensive understanding of morphosyntactic interactions. The pedagogical implications emphasize the importance of integrative learning that connects morphology with syntax to improve students' linguistic competence. Morphosyntactic error analysis revealed a systematic pattern stemming from a lack of understanding of the relationship between word form and function and regional language interference. Handling strategies include explicit learning, counterproductive approaches, and the use of adaptive technology. This research contributes to the development of Indonesian linguistic theory and the improvement of the quality of language learning. Keywords: Morphology; Syntax; Indonesian Learning